Hoot [large type] - Hiaasen, Carl (Thorndike Press large print striving reader collection., 2020)
Roy, who is new to his small Florida community, becomes involved in another boy's attempt to save a colony of burrowing owls from a proposed construction site of a new pancake restaurant.